ASSESSMENT OF DEPRESSION-LIKE BEHAVIOR AND ANHEDONIA AFTER REPEATED CYCLES OF BINGE-LIKE ETHANOL DRINKING IN MALE C57BL/6J MICE - Olney, Jeffrey J. (Pharmacol Biochem Behav, 2018)
Psychological depression is frequently linked to alcohol abuse and even serves as key indicators of an alcohol use disorder (AUD). This relationship is supported by preclinical findings in which depression-like phenotypes develop in animals exposed to chronic intermittent ethanol vapor, a common preclinical model of alcohol dependence. However, the emergence of these maladaptive phenotypes following repeated binge-like ethanol drinking remains relatively unexplored. The purpose of this study was to evaluate depression-like behaviors associated with binge-like consumption in mice. Using the drinking-in-the-dark (DID) paradigm, we examined the impact of multiple binge-like cycles (1, 3, or 6) on depression-like behaviors in the forced swim test (FST) and sucrose preference as a test for anhedonia. We also assessed the effect of repeated binge cycles on the consumption of bitter and sweet tastants over a range of concentrations. Results indicated that binge-like ethanol drinking did not lead to depression-like behavior as repeated cycles of DID did not alter sucrose consumption or preference nor did it impact time spent immobile during the FST. Animals that experienced six cycles of DID showed increased quinine consumption and increased quinine preference, which may be indicative of an escalated preference for tastants that resemble the gustatory aspects of ethanol. Interestingly, an unexpected ~20% increase in hypermobility was observed after three cycles of binge-like ethanol drinking. Although the FST is most frequently used to model depression-like behavior, emerging evidence suggests that increased hypermobility during the FST could be indicative of an inability to cope in a stressful situation, suggesting that repeated ethanol exposure in the present experiment transiently enhances stress reactivity.